Protection and remedies for Malaysian consumers in land fraud - Sufian, Azlinor; Mohamad, Nor Asiah (2010)
The case of Adorna Properties v Boonsom Bonyanit (2000), the real registered land proprietor lost her land due to fraud committed by the “criminal”. Despite there is allegation that the transaction was acquired through unlawful means or fraud, the court confirmed the right of the person whose name appeared as the registered owner on the land. Thus the court in Boonsom Bunyanit seemed to acknowledge that Malaysia is following the immediate indefeasibility even though it is already well established that Malaysia recognized deferred indefeasibility. The case of Boonsom became a nightmare to consumers. However in Tan Yin Hong (2010) the Federal Court regards Boonsom’s case is no longer a good law. Even though decision in Tan Yin Hong may be considered as a relief to land proprietors, as consumers it is very important for them to know the legal protection and remedies available in case of land fraud. This paper will look into the reasons why land fraud occurs, the statutory protection available for consumers in land fraud cases in which it may contain among others in the National Land Code 1965 and Penal Code 1950 as well as the legal remedies that may be offered to consumers.